PENERAPAN MODEL PEMBELAJARAN PEMECAHAN MASALAH BERBANTUAN LKS DALAM UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA SISWA - I Komang Sukendra (LP3M Universitas PGRI Mahadewa Indonesia, 2020)
The purpose of this study was to determine whether the diffractive learning strategy assisted with worksheets can increase student activity and mathematics learning outcomes. This type of research is classroom action research. The research subjects of class X MIA 3 SMA Negeri 7 Denpasar in the 2018/2019 academic year. The research object of frogressive diffraction learning was assisted by worksheets. Each cycle consists of four stages, namely: the planning stage, the implementation stage, the observation or observation stage, and the reflection stage. The results of the study for student learning activities in cycle I were 9.92, and in silkus II were 16.80. Student learning outcomes for an average cycle I of 6.48 and cycle II of 8.02. The absorption capacity in the first cycle was 64.8% and the second cycle was 80.2%. Classical mastery learning in cycle I was 20.0% and cycle II was 85.7%. So the application of progressive differentiation learning strategies assisted by student worksheets in mathematics learning can improve learning activities and student learning outcomes of class X MIA 3 SMA Negeri 7 Denpasar.